Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.12688/f1000research.20399.2
|View full text |Cite
|
Sign up to set email alerts
|

The development of mouthwashes without anti-gonococcal activity for controlled clinical trials: an in vitro study

Abstract: Background: The oropharynx plays a major role in the development and spread of antimicrobial resistant Neisseria gonorrhoeae among men who have sex with men. Trials are currently assessing the efficacy of bactericidal mouthwashes as possible therapeutic or preventive options against these pharyngeal gonococcal infections. Controlled clinical trials require the use of a placebo mouthwash without anti-gonococcal activity. So far, no such placebo mouthwash has been described. We describe the development of a mout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…For example, chlorhexidine is an antiseptic that has broad-spectrum antibacterial activity ( 39 ); therefore, one may expect a chlorhexidine mouthwash to have more impact on the oral microbiome compared to milder mouthwashes. Additionally, while exposure to Listerine Zero for 10 s or longer has been shown to inhibit the growth of N. gonorrhoeae in vitro , short-term exposure to Biotène (i.e., 5 min or less) has limited activity against N. gonorrhoeae ( 15 , 17 ). This may indicate that the two mouthwashes have different antimicrobial activity, which could explain, in part, why we observed differences in how the two mouthwashes affected the oropharyngeal microbiota composition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, chlorhexidine is an antiseptic that has broad-spectrum antibacterial activity ( 39 ); therefore, one may expect a chlorhexidine mouthwash to have more impact on the oral microbiome compared to milder mouthwashes. Additionally, while exposure to Listerine Zero for 10 s or longer has been shown to inhibit the growth of N. gonorrhoeae in vitro , short-term exposure to Biotène (i.e., 5 min or less) has limited activity against N. gonorrhoeae ( 15 , 17 ). This may indicate that the two mouthwashes have different antimicrobial activity, which could explain, in part, why we observed differences in how the two mouthwashes affected the oropharyngeal microbiota composition.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, the use of antiseptic mouthwash has been proposed as an intervention to reduce gonorrhea transmission in MSM ( 7 , 13 ). Previous in vitro studies have shown that antiseptic mouthwash can inhibit N. gonorrhoeae growth ( 14 , 15 ), and a small number of clinical trials have examined the use of mouthwash for the prevention and/or treatment of oropharyngeal gonorrhea ( 14 , 16 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Its antibacterial mechanism of action is based on damaging the bacterial cytoplasmic membrane and subsequent leakage of cytoplasmic components ( Cieplik et al, 2019 ). In vitro studies have established that N. gonorrhoeae is highly susceptible to killing by chlorhexidine ( Rabe and Hillier, 2000 ; Victoria et al, 2018 ; Van Dijck et al, 2020 ). However, a recent clinical trial was ended early since twice daily gargling with chlorhexidine for six days failed to eradicate N. gonorrhoeae in the oropharynx ( Van Dijck et al, 2021a ).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] As a consequence, several authors have proposed that antiseptic mouthwashes may be used to prevent or treat oropharyngeal gonorrhea. 1,4,5 In vitro studies have established that Ng is highly susceptible to killing by mouthwashes such as Listerine 6,7 and chlorhexidine, [8][9][10] and a randomized controlled trial in men with culture-positive oropharyngeal gonorrhea found that Ng could not be cultured in a significant proportion of men 5 minutes after a single gargling session with Listerine. 7 Despite these initial encouraging results, 3 randomized clinical trials have found that Listerine failed to prevent (PReGo 4 and OMEGA1 11 ) or treat (OMEGA2 5 ) oropharyngeal gonorrhea.…”
mentioning
confidence: 99%
“…Nevertheless, chlorhexidine's strong in vitro bactericidal effect suggests that it could be more effective than Listerine in killing Ng in the oropharynx. 6,8,13,14 The aim of this single-arm, open-label pilot study was therefore to assess whether a chlorhexidine mouthwash could eradicate Ng from the oropharynx of asymptomatic men.…”
mentioning
confidence: 99%